Volcano Stratigraphy of Kulon Progo Super Brigade - Hartono, Hill Gendoet; Sugarbo, Oky (Indonesian Journal on Geoscience, 2026)
The research location is in the Kulon Progo Mountains, west of the Daerah Istimewa Yogyakarta province and part of Central Java. Several previous researchers have discussed the stratigraphy of the Kulon Progo Mountains region, following the rock unit grouping rules that have evolved from the past to the present. Approaches to clarify the geological conditions of the Kulon Progo Mountains and efforts to comply with Indonesian Stratigraphic Code standards are continuously being carried out. The purpose of this study is to identify volcanic stratigraphic units in the Kulon Progo Mountains using the principles and concepts of volcanic stratigraphy. The research methods used were surface geology research and remote sensing. The research conducted through surveys or field visits at specific locations was identified as key areas of interest. Remote sensing and topographic map analysis were also conducted to delineate the distribution of volcanic rocks and the boundaries of volcanic stratigraphic units. Laboratory analysis was conducted to strengthen the interpretation of volcanic rock genesis and thus support the interpretation of the presence of volcanoes in the study area. Comprehensive analysis is used to determine the location of ancient eruption sources, descriptions of coherent and pyroclastic lava, and the origin of volcanoes, which have developed quite significantly, as well as the volcanic stratigraphic units in the study area. The volcanic stratigraphic units of the Kulon Progo Mountains from the early to late activity periods are grouped into the Gajah Brigade, Ijo Brigade, and Menoreh Brigade stratigraphic units. The collection of volcanic stratigraphic units from the three brigades that built the Kulon Progo Mountains and were mapped at a scale of 1:100,000 is called Super Brigade Kulon Progo. The Gajah Brigade Unit is in the center, the Ijo Brigade Unit is in the south, and the Menoreh Brigade Unit occupies the northern part of Super Brigade Kulon Progo, which is in a relatively northeast-southwest trend. The Gajah Brigade covers the north side of Crown Bujel, which is bounded by a long escarpment that opens to the west, and the flat Crown Pencu is bounded by a curved escarpment that also opens to the west. Ijo Brigade is in the southern part of the Kulon Progo Mountains and has a relatively rounded shape, bounded by steep escarp- ments, especially on the north and east sides. The geological elements of the ancient volcano Ijo Brigade appear much clearer than those of the other brigade, so it is estimated that it is younger than the time the Gajah Brigade was formed. Ijo Brigade covers two ancient volcanic bodies, namely Ijo Crown in the north and Kukusan Crown in the south. Menoreh Brigade is in the northern part of the Kulon Progo Mountains and is the youngest of the three brigades that built Super Brigade Kulon Progo. The Menoreh Brigade encompasses the Gupit Crown, which is a dacite intrusive body, the smallest in diameter and the lowest in topography among the existing Crowns. The stratigraphy of the ancient volcanoes of the Kulon Progo Mountains is arranged by volcanic unit levels from large to small, namely Super Brigade, Brigade, and Crown.